2020
DOI: 10.3389/fpls.2020.476251
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of a Sucrose Synthase Gene Indirectly Improves Cotton Fiber Quality Through Sucrose Cleavage

Abstract: The study aims to improve fiber traits of local cotton cultivar through genetic transformation of sucrose synthase ( SuS ) gene in cotton. Sucrose synthase (SuS) is an important factor that is involved in the conversion of sucrose to fructose and UDP-glucose, which are essential for the synthesis of cell wall cellulose. In the current study, we expressed a synthetic SuS gene in cotton plants under the control of a CaMV35S promoter. Amplification of an 813-bp fragme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 61 publications
1
14
0
Order By: Relevance
“…It was found that MBI7747 showed an SNP and a complete Indel of 55 bp than its parents CCRI45 and Hai1. This finding strengthens the previous hypothesis that this gene might contribute a significant addition to the improvement of fiber length just like other transgenes such as expansin (Bajwa et al, 2015), cellulose synthase (Arioli et al, 1998), sucrose synthase (Ahmed et al, 2020), and actin (Ahmed et al, 2018a).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…It was found that MBI7747 showed an SNP and a complete Indel of 55 bp than its parents CCRI45 and Hai1. This finding strengthens the previous hypothesis that this gene might contribute a significant addition to the improvement of fiber length just like other transgenes such as expansin (Bajwa et al, 2015), cellulose synthase (Arioli et al, 1998), sucrose synthase (Ahmed et al, 2020), and actin (Ahmed et al, 2018a).…”
Section: Discussionsupporting
confidence: 90%
“…For example, CaMV35S promoter is widely adopted and reported efficient transformation of foreign gene into the cotton plant. In a recent study of sucrose synthase (SuS) gene transformation in cotton, CaMV35S promoter is used and resulted in significant improvement in fiber quality (Ahmed et al, 2020). This has been proved through various studies that revealed the relative expression of the tissue specific and constitutive promoters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Jiang et al (2012) demonstrated that over-expressing GhsusA1 , a cotton SuSy gene, increased the thickness of the secondary cell wall and overall fiber strength, which indicates that a sucrose signal is involved in controlling cellulose biosynthesis in the development of cotton fiber ( Jiang et al, 2012 ). When this synthetic SuS y gene is overexpressed in cotton, the transgenic cotton plants showed longer fiber length, enhanced fiber strength, and increased cellulose contents ( Ahmed et al, 2020 ). The cell wall invertase (CWIN) is responsible for sucrose cleaving into fructose and glucose, while the expression levels of GhCWIN are significantly more highly expressed at 5 and 10 DPA than 15 and 20 DPA ( Wang and Ruan, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…The suppression of GhSusA1 led to reduced fiber quality, boll size, and seed weight, while the overexpression of this gene increased fiber length and strength [ 59 ]. In addition, the overexpression of a potato SuSy and a synthetic SuSy gene also improved cotton fiber quality [ 60 , 61 ]. Therefore, PM-associated SuSy are important for cotton fiber development, and could be used for improving fiber products.…”
Section: The Regulation Mechanism Of Membrane Proteins In Cotton Fiber Developmentmentioning
confidence: 99%